Assessing the Competitiveness of Malaysia and Indonesia Palm Oil Related Industry - Mohammad Affendy, Arip; Lau, Sim Yee; Thien, Sie Feng (Billion Brains, 2013)
This study aims to examine the comparative advantage of palm oil related products in Malaysia and Indonesia using the Revealed Comparative Advantage (RCA) approach introduced by Balassa (1989). Our findings based on 20 related palm oil products show the following. Firstly, the RCA indexes for these products in both countries are unstable during the analytical period. Secondly, Malaysia is more competitive than Indonesia in most of the downstream palm oil related industries such as S3-42229, S3-42249, S3- 43122, S3-51217, S3-51222 and S3-55419. Thirdly, in some industrial activities, both countries show that the development of certain palm oil industrial products are consistent with the product life cycle (PLC) theory. They are mainly upstream industrial products such as the S3-08138, S3-42221, S3- 42231, S3-42239, and S3-42241 commodities. As the biggest producers of palm oil, both countries should put more emphasis on downstream industrial products--which are of higher value-added--taking the benefit of their comparative advantage in upstream industries.